HUBUNGAN RAJA DENGAN RAKYAT DALAM KOHESI SOSIAL MELAYU ISLAM - Wan Zailan Kamaruddin Ali (TEMALI : Jurnal Pembangunan Sosial, 2019)
In the context of the Malay world, Islam and the Malays are not inseparable. Islam is the "a-gama", "a way of life," "system and way of life" or more precisely, "al-Din" and Malay are also race and adherents. It seems that Islam is strong and strengthening the Malays, while Malays are strong and strengthened with Islam. In the context of Taj al-Salatin, the issue of leadership (al-Imamah wa al-Khilafah) or the issue of the rulers (al-Ra 'i wa al-Ra'iyyah) was seriously debated. Is it in parallel with the Qur'an and al-Hadith, and fulfilling the reference and the framework of Islamic political thought is interesting to study. Apparently, it also presents examples from non-Islamic sources that certainly invite controversy. Collected data is analyzed in a comparative basis based on qualitative methods. The main objective of this article will be on leadership issues, the rulership of the people (al-ra'i wa al-ra'iyyah) from the perspective of Islamic Political Thoughts with the results hoped to help Islamic politics and Malay politics to go along and align to fulfill and realize Islam as "Din al-Hayat" and Malay as one of the ummah of "umam muslimah" who became his supporters and supporters to achieve his excellence and glory not only in the context of the Malay World and the Islamic World.